In-vitro Analysis of Antifungal Activity of Epigallocatechin-Gallate: Preliminary Study. (September 2013) - Guida, A.; Lucchese, A.; Minervini, G.; De Gregorio, V.; Coretti, L.; Grimaldi, E.; Minervini, D.; Serpico, R.; Donnarumma, G.
Oral candisosis is an heterogeneous group of diseases, caused by different species of Candida fungus. The incidence of drug-resistant species is increasing dramatically; furthermore, in recent years higher incidences of non-albicans and antimycotic-resistant species of Candida have been reported, thus increasing necessity of a non-antibiotic agent, which should be both highly effective and safe. It has been showed that the main polyphenols component of green tea, epigallocatechin-gallate (EGCG), has antibacterial activity; recently, it has been reported its antifungal activity too. We tested the effectiveness of a 0.20% EGCG (TEAVIGO®) gel, a non-pharmaceutical product suitable for oral in vivo use, on four species of Candida yeast (C.albicans, Cparapsilosis, C.tropicalis, C.glabrata), evaluating its antifungal activity and its capacity to inhibit biofilm formation. The EGCG gel showed a remarkable activity against C. parapsilosis and C. tropicalis. This preliminary study confirms EGCG effectiveness on fungi; for this reason, a product with such a low concentration of EGCG could be used with no side-effect for every-day oral hygiene. Anyway, mechanisms of antifungal activity of EGCG are not comprehended and need further studies to better understand the reasons of some Candida species' resistance.